Continuous Dependence for the Boussinesq Equations under Reaction Boundary Conditions in R2 - Jincheng Shi; Yan Liu (Mathematics, 2022)
In this paper, we studied the continuous dependence result for the Boussinesq equations. We considered the case where <semantics>Ω</semantics> was a bounded domain in <semantics>R2</semantics>. Temperatures T and C satisfied reaction boundary conditions. A first-order inequality for the differences of energy could be derived. An integration of this inequality produced a continuous dependence result. The result told us that the continuous dependence type stability was also valid for the Boussinesq coefficient <semantics>λ</semantics> of the Boussinesq equations with reaction boundary conditions.